Research Training and Gender as Determinants of Education Undergraduate Students' Attitude Towards Research in Universities in Cross River State, Nigeria. - Odiong, Jacob Esu Thomas; Edet Sunday Nyong; Nkereuwem Edet (African Journal of Behavioural and Scale Development Research, 2020)
Conducting a study as a mandatory requirement for graduation by students in universities underscores the importance of research in national progress. However, a number of undergraduate students tend to be nervous by this demand. This study examined the influence of research training and gender on undergraduate students' attitude towards research in the universities in Cross River State, Nigeria. The survey design was adopted. The population was 2,048 final year students of the faculties of education, University of Calabar and the Cross River University of Technology for the 2013/2014 session. Proportionate stratified and purposive sampling techniques were adopted. 20% of the population (410 students) were sampled. The close-ended questionnaire on a 4-point Likert type scale was used for data collection. From the Independent t-test analysis, gender does not significantly influence attitude towards research. However, research training does. There was a need for the universities to regularly organize research orientation to enable the students gain required research skills prior to their research work